1979
DOI: 10.1103/physrevd.19.2827
|View full text |Cite
|
Sign up to set email alerts
|

Interior magnetohydrodynamic structure of a rotating relativistic star

Abstract: We study the interior magnetohydrodynamic structure of a rotating stationary axisymmetric neutron star. We assume the fluid is ideal, infinitely conducting, and flows only azimuthaly. We justify this assumption by considering in detail the superfluid physics in the interior. We obtain some of our results by taking a certain limit of previously discovered magnetohydrodynamic conservation laws. We show that the angular velocity, electric and magnetic potentials, and the red-shifted chemical potential are constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…A second consideration is whether or not the initial model should be an equilibrium model. In general, if one tries to construct a stationary model without meridional currents and assuming an isentropic flow, the only possible magnetic field configuration is poloidal (see Bekenstein & Oron 1979). Stationary models of magnetized stars have been computed under these assumptions by Bocquet et al (1995).…”
Section: Initial Datamentioning
confidence: 99%
“…A second consideration is whether or not the initial model should be an equilibrium model. In general, if one tries to construct a stationary model without meridional currents and assuming an isentropic flow, the only possible magnetic field configuration is poloidal (see Bekenstein & Oron 1979). Stationary models of magnetized stars have been computed under these assumptions by Bocquet et al (1995).…”
Section: Initial Datamentioning
confidence: 99%
“…Bekenstein and Oron [19,20] showed that a stationary axisymmetric system has several conserved quantities along each flow line. This is a general relativistic generalization of Ferraro's integrability condition [40,41,42].…”
Section: A Basic Equations For General Relativistic Magnetohydrodynamentioning
confidence: 99%
“…General relativistic effects are sizable in the interior of a neutron star, so that any quantitative investigation of the magnetars has to be based on general relativistic magnetohydrodynamics (MHD) [17,18,19,20]. Therefore, we have to solve the matter and electromagnetic field configurations in a curved spacetime, and have to take account of the electromagnetic energy-momentum as a source of the gravitational field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus a fully consistent relativistic magnetohydrodynamic model is required to learn the evolution of a rotating neutron star's interior. A significant step in this direction has been the work of Bekenstein and Oron [3] in which interior hydromagnetic structure of a rotating neutron star's interior is coupled to gravitational interaction. Invoking electrons theory of the conductivity of matter, it has been argued by Bekenstein and Oron [4] that the electric field vanishes in a frame comoving with the fluid if the electric current is to be maintained finite in the limit of infinite electrical conductivity.…”
mentioning
confidence: 99%